Feed efficiency in Alpine and Saanen lactating goats consuming a barn-dried hay obtained in a sustainable goat farming system (Patuchev) - Giger-Reverdin S.; Sauvant D.; Caillat H. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
In France, the aim of sustainable goat farming systems is to use more forages as a tool to increase feed self-sufficiency and to produce cheeses of high value. Thus, it is worthwhile to check the factors of variation of feed efficiency in dairy goats fed barn-dried hay produced in a system including pastures. Twenty-two mid-lactating dairy goats (11 Alpine and 11 Saanen) received ad libitum barn-dried hay obtained from fields at Inra Lusignan and a concentrate separately with a forage/concentrate ratio 55/45. Dry matter intake (DMI) expressed on a body-weight basis was higher for Alpine than for Saanen. Organic matter digestibility was not influenced by level of intake and was mainly function of indigestible cell wall. Fat and protein corrected milk yield (FPCMY) was directly proportional to digestible organic matter intake (DOMI). Feed efficiency (1.38 ± 0.137) or ratio of FPCMY/DMI is the product of the digestive efficiency (DOMI/DMI) by the metabolic efficiency (FPCMY/DOMI). It was mainly correlated to metabolic efficiency (r = 0.97), but not to digestive efficiency, probably due to its low range of relative variation. It increased with the level of milk production and tended to be higher for Saanen than for Alpine goats when milk production was used as a covariate. Moreover, the ratio “N output in milk/N intake” with the tested diet was directly proportional to feed and metabolic efficiencies. Thus, in our context, high producing animals have a better feed efficiency.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)